Evaluating PWIM and GTM in Teaching English Basic Structure for EFL Undergraduates - Rosyada, Amrina; Febriyanti, Rina Husnaini (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research aimed at evaluating the use of the Picture Word Inductive Model (PWIM) and Grammar Translation Method (GTM) in teaching English Basic Structure for EFL undergraduates. Eighty-four students were randomly chosen as a sample from over 400 EFL undergraduates students in the second semester of the English Education Program. Furthermore, the samples were grouped into two classes, 43 students in the PWIM group and 41 students in the GTM group. The research employed the mixed-method research of convergent parallel design. The efficacy of the PWIM and GTM was investigated in terms of learners' ability to develop structured sentences. The PWIM, as a new experience in teaching Basic Structure, was administered in two cycles. On the other hand, the GTM as the conventional teaching method was implemented within six sessions. In PWIM, two poster pictures were modeled as the instruments. At the end of the treatment, a post-test of structured sentences was assigned in both groups. The test consisted of 25 error analysis questions. As the results, in PWIM class, the highest score was 98, the lowest score was 66, and the average score was 78.1. Meanwhile, in the GTM class, the highest score was 96, the lowest score was 42, and the average score was 64.6. Moreover, the research indicated that most students were enthusiastic in the learning process and experienced different exciting learning process through PWIM. It can be said that applying PWIM as the new teaching method in teaching English Basic Structure is needed to enrich and broaden students' learning outcomes.